Leading change : with a new preface by the author - Kotter, John P. , 1947- (Boston, Massachusetts : Harvard Business Review Press, 2012)
From the ill-fated dot-com bubble to unprecedented M & A activity to scandal, greed, and, ultimately, recession -- we've learned that widespread and difficult change is no longer the exception. It's the rule. The author's eight-step process for managing change with positive results has become the foundation for leaders and organizations across the globe. By outlining the process organizations have used to achieve transformational goals and by identifying where and how even top performers derail during the change process, the author provides a practical resource for leaders and managers charged with making change initiatives work.
1. Transforming organizations: why firms fail -- 2. Successful change and the force that drives IT -- 3. Establishing a sense of urgency -- 4. Creating the guiding coalition -- 5. Developing a vision and strategy -- 6. Communicating the change vision -- 7. Empowering employees for broad-based action -- 8. Generating short-term wins -- 9. Consolidating gains and producing more change -- 10. Anchoring new approaches in the culture -- 11. The organization of the future -- 12. Leadership and lifelong learning
First published in 1996
Includes new preface by the author
Keywords: Industrial organization; Leadership; Organizational change; Strategic planning